Impact of quality-led design on real estate value: a spatiotemporal analysis of city centre apartments. Issue 4 (1st October 2016) - Nase, Ilir; Berry, Jim; Adair, Alastair
Abstract: This paper estimates the impact of quality design attributes on real estate value through empirical investigation of the owner-occupied multifamily residential sector. The methodological design is based on spatiotemporal modelling using a unique data-set of 424 Belfast City Centre apartments sold during the period 2000–2008. The key findings indicate that urban scale aspects of quality such as connectivity and vitality associated with building density add to real estate value. At the building level, quality features highly valued by home buyers are namely appropriateness of material quality, fenestration and massing to the surroundings. These key criteria are considered to have a significant visual perception compared to more complex concepts such as identity, material choice and overall condition. The contribution to knowledge involves extending the hedonic model to incorporate a wider selection of design quality variables; and improving estimation through the use of spatiotemporal modelling.